Intrinsic and extrinsic resistive switching in a planar diode based on silver oxide nanoparticles - Kiazadeh, Asal (2012)
Resistive switching is investigated in thin-film planar diodes using silver oxide nanoparticles capped in a polymer. The conduction channel is directly exposed to the ambient atmosphere. Two types of switching are observed. In air, the hysteresis loop in the current–voltage characteristics is S-shaped. The high conductance state is volatile and unreliable. The switching is mediated by moisture and electrochemistry. In vacuum, the hysteresis loops are symmetric, N-shaped and exhibit a negative differential resistance region. The conductance states are non-volatile with good data retention, programming cycling endurance and large current modulation ratio. The switching is attributed to electroforming of silver oxide clusters.